2022
DOI: 10.1002/eap.2651
|View full text |Cite
|
Sign up to set email alerts
|

Scale dependence of coral reef oases and their environmental correlates

Abstract: Identifying relatively intact areas within ecosystems and determining the conditions favoring their existence is necessary for effective management in the context of widespread environmental degradation. In this study, we used 3766 surveys of randomly selected sites in the United States and U.S. Territories to identify the correlates of sites categorized as "oases" (defined as sites with relatively high total coral cover). We used occupancy models to evaluate the influence of 10 environmental predictors on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In contrast, all the Lower Keys patch reefs have maintained positive carbonate budgets despite the suite of disturbances in recent decades (Figure 1; Figure S2 and Table S6). We hypothesize that the combination of relatively low water clarity (lower irradiance) of inshore environments on the FKRT, in general, and distance of the Lower Keys patch reefs from tidal passes to the Florida Bay, in particular, have resulted in these reefs having high resilience to both high and low thermal anomalies, respectively, suggesting that they may be important targets for future management (Barnes et al, 2015; Elahi et al, 2022; Guest et al, 2018; Sully & van Woesik, 2020). We note that SCTLD was first observed in the Lower Keys during the final year of our study in 2019, so we likely did not capture its full impact on coral cover at our sites there.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, all the Lower Keys patch reefs have maintained positive carbonate budgets despite the suite of disturbances in recent decades (Figure 1; Figure S2 and Table S6). We hypothesize that the combination of relatively low water clarity (lower irradiance) of inshore environments on the FKRT, in general, and distance of the Lower Keys patch reefs from tidal passes to the Florida Bay, in particular, have resulted in these reefs having high resilience to both high and low thermal anomalies, respectively, suggesting that they may be important targets for future management (Barnes et al, 2015; Elahi et al, 2022; Guest et al, 2018; Sully & van Woesik, 2020). We note that SCTLD was first observed in the Lower Keys during the final year of our study in 2019, so we likely did not capture its full impact on coral cover at our sites there.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are still some "oases" within the degraded reefscapes of the Florida Keys (Figure 1d; Courtney et al, 2020;Elahi et al, 2022;Guest et al, 2018), our estimate of average reefaccretion potential on the FKRT at present of 0.20 mm year −1 is substantially lower than most other locations around the world (Cornwall et al, 2021;Perry et al, 2018). With the putative additional contributions of physical and chemical erosion, it is likely that reef building on the FKRT has declined even more dramatically than our study suggests, and erosion is now the dominant process regionwide (i.e., reef accretion is estimated at −0.93 mm year −1 , on average).…”
Section: Quantifying Changes In Reef Accretionmentioning
confidence: 99%
“…Perry et al, 2018) using the equation suggested by Kinsey (1985) and regional reef-framework porosity estimates from Toth et al (2018a). We emphasize that reefaccretion potential likely represents a high-end estimate of realized accretion rates because it does not incorporate nonbiological physical erosion or chemical dissolution, which Toth et al (2022) estimated likely contributes at least an additional ~1 mm y -1 of erosion in the Florida Keys. Furthermore, the omission of some bioeroding taxa from our surveys, the possibility that sponge abundance has increased since they were last surveyed by CREMP in 2009, and the lack of co-located parrotfish data, suggest that our estimates of total bioerosion may be conservatively low and that reef-accretion potential is likely lower than our study indicates.…”
Section: Methodsmentioning
confidence: 90%
“…We use those data to quantify the impacts of SCTLD on gross and net carbonate production, bioerosion, and reef-accretion potential as well as species-level contributions to carbonate production throughout its endemic period in the region (2017-2022; Figure 1). The carbonate budgets were calculated in R Studio (R Core Team, 2023; using the method proposed by Toth et al (2022), which is an adaptation of the ReefBudget v2 methodology (Perry and Lange, 2019). All data, calculations, and necessary modifications to the ReefBudget v2 methodology are discussed in detail in and data and code for new analyses included in this study are provided in version 1.1 of the USGS software release by .…”
Section: Methodsmentioning
confidence: 99%
“…As restorations continue to scale up spatially, new approaches will be needed to evaluate changes in ecosystem functions and services at larger spatial scales. In coral reef systems, the applications of explanatory and predictive models for both ecology and hydrodynamics have increased over the past several decades (e.g., Chen et al, 2020; Elahi et al, 2022; Madin et al, 2020; Yu et al, 2018). Considerable expertise and many tools have been developed for ecological, hydrodynamic, and engineering processes specific to coral reefs.…”
Section: Coral Restoration For Coastal Protectionmentioning
confidence: 99%